Xenophobia within the Immigrants in the Netflix’s Squid Game Series - Elsa, Rizky Femilya; Husein, Rahmad; Lubis, Fauziah Khairani (Language Circle: Journal of Language and Literature, 2024)
The study aims to find out about the types of xenophobia, and its realization as well as the justification of that matter which appears in some scenes by the characters of Netflix’s the Squid Game series. The analysis used descriptive qualitative as a method to meet the objectives of the study. The source of the data in this study is taken from episodes 1 to 6 of the Squid Game series aired on Netflix. Xenophobia which mostly happened to the immigrants found in the series due to the existence of the two immigrant characters. To analyze the data, the theory of types of xenophobia which proposed by Harris (2002). The isolation hypothesis is the most dominant type found in the study due to feeling isolated in most of the scenes just because they are immigrants and they feel like they have no right to mingle with the natives.